Good Governance as a Mediator: Analyzing the Influence of Financial Governance and Internal Control on Performance Accountability - Lisnawati, Lisnawati; Surwanti, Arni; Gunarto, Muji (International Journal of Marketing & Human Resource Research, 2026)
Abstract This study aims to examine the relationship between financial governance and internal control, and to analyze how good governance mediates the relationship between these two constructs and performance accountability. The research employs a quantitative method in which financial governance and internal control serve as independent variables, performance accountability as the dependent variable, and good governance as the mediating variable. The population of this study comprises 239 employees of the BRPPUPP. Primary data were obtained from questionnaires distributed to respondents, and secondary data were collected from institutional records. The results indicate a significant and positive relationship between financial governance and internal control on performance accountability, and that the good governance variable mediates this relationship